Systems thinking, spirituality and Ken Wilber: beyond New Age - Kamppinen, Matti (Approaching religion, 2015)
Systems thinking is a general worldview concerning the nature of reality. It sees the world as composed of systems, and all particular entities populating reality as linked with other entities - the emergence of new properties denies the flatland of plain materiality, and generates entities of a higher order. Spirituality in historical and modern traditions has minimally amounted to relating oneself to a larger or higher systemic whole, which confers meaning to particular cases of existence. In some religious traditions this larger systemic whole has been understood as a transcendental sphere of existence, whereas in other religious and spiritual traditions it has been seen as an immanent thatness. The search for spirituality and wisdom has never been confined to religious traditions, but has inspired other systems thinkers as well, for example in philosophy, the New Age movement, in developmental psychology, biology, or futures research. The American philosopher and theoretical psychologist Ken Wilber (b. 1949) has discussed, re-interpreted and synthesized various views on spiritual development as well as systems thinking and has provided input for the New Age movement, comparative religion, developmental psychology, and world philosophy. In this article we will discuss the relationship between systems thinking and spirituality and will assess Ken Wilber’s contribution to their conceptualization.